The Brain Drain of Moroccan IT Profiles: An Exploratory Qualitative Study within Y and Z Generations - Gassemi, Karim; Aniba, Loubna (International Review of Management and Marketing, 2024)
The objective of this study is to identify and analyze the main factors driving young Moroccan IT professionals to emigrate. Through qualitative exploratory research, we aim to explore the Brain Drain within individuals belonging to the Y and Z generations. The theoretical model of this study was based on Lee’s (1996) general framework. The research methodology was based on conducting semi-structured interviews with 22 young IT professionals who have either already emigrated with significant years of experience. This qualitative approach allows us to understand the multifaceted nature of their decision-making process. Through the data analysis, we have identified three dichotomous factors that serve as both push and pull factors, contributing to the phenomenon of brain drain among young IT professionals in Morocco. These factors include economic considerations, professional aspirations and social dynamics. Each factor plays a distinct yet interconnected role in shaping individuals’ decisions to emigrate.